2022
DOI: 10.1002/er.8168
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of tunable polypyrrole‐based composites on carbon fabric for wide potential window aqueous supercapacitor

Abstract: Facile one-step electrochemical synthesis of a novel graphitic oxide/polypyrrole/2-acrylamido-2-methyl-1-propanesulfonic acid composite on carbon fabric were described for development of an efficient positive electrode for supercapacitor applications. The 2-acrylamido-2-methyl-1-propanesulfonate monomers behave as dopant in 3D polypyrrole network formed by synergetic coupling with graphitic oxide. Their free acrylic groups interact with each other to form polymer-hydrogel-layer on the external surface that fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…This showed that the diffusion rate of mobile ions in the 1000th cycle increased compared to the situation in the initial and 2000th cycles. 16,43,74,[78][79][80] The Cdl value, on the other hand, was at the highest level after 1000 cycles, in this case, it showed that the interaction at the electrode/electrolyte interface was the highest and the double layer capacitance is the highest in these cycles. 16,43,74,[81][82][83][84] To determine the charge-discharge behavior of the supercapacitor, galvanostatic charge-discharge tests were performed to PANI/SGO/NGO-3 including supercapacitor at a current density of 0.1 A g −1 between 0 and 1.5 V (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…This showed that the diffusion rate of mobile ions in the 1000th cycle increased compared to the situation in the initial and 2000th cycles. 16,43,74,[78][79][80] The Cdl value, on the other hand, was at the highest level after 1000 cycles, in this case, it showed that the interaction at the electrode/electrolyte interface was the highest and the double layer capacitance is the highest in these cycles. 16,43,74,[81][82][83][84] To determine the charge-discharge behavior of the supercapacitor, galvanostatic charge-discharge tests were performed to PANI/SGO/NGO-3 including supercapacitor at a current density of 0.1 A g −1 between 0 and 1.5 V (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…In addition, the functional groups of the AY17 dye enabled the development of redox behaviour of the PANI. In addition, -Cl bonds, N-N bonds in the ring structure, and sulfonate groups (SO3 -) in the AY17 dye structure strengthened the delocalization in the chain structure, supporting the redox behavior of PANI (36). PANI, PANI/AY17, PANI/MWCNTs, and PANI/MWCNT/AY17-3 electrode Nyquist curves fitted to a simple circuit model are shown in Figure 3d (inset in Figure 3d).…”
Section: Electrochemical Analysismentioning
confidence: 67%
“…The fundamental peaks of Cu and O are observed in all the EDS spectrums. The element S in the EDS spectrum of copper, which was also anodized in sulfuric acid electrolyte solution, originated from the electrolyte in the medium (36). Atomic percentage of Cu(30)/ASA(0.02) compared to atomic percentage of Cu (30), it was observed that the percentage of element S increased significantly with the addition of ASA.…”
Section: Resultsmentioning
confidence: 95%